Vehicle Detection And Vehicle Tracking Applications On Traffic Video Surveillance Systems: A systematic literature review - Ay, Sevinç (Prof.Dr. İskender AKKURT, 2024)
The number of vehicles in traffic and the use of traffic surveillance systems are increasing day by day. This situation has revealed the necessity of control and analysis processes on traffic surveillance systems. Vehicle detection and vehicle tracking studies for the purpose of analyzing video sequences obtained from surveillance systems have recently become a popular field of study. Despite the increase in studies in this field, the aimed level has not been reached. Many reasons such as weather changes, day-night difference, vehicles blocking each other in traffic, background complexity make vehicle detection and tracking difficult. This study is presented to guide researchers who want to work in the field. In order to determine the common trends of the studies and to analyze the studies, a data set was created by searching the Web of Science database using the keywords "vehicle detection" and "vehicle tracking". In order to analyze the obtained data, the Voswiever (version 1.6.20) program and the R studio programs "bibliometrix" package and the biblioshiny application were used. © IJCESEN.
Keywords: Artificial Intelligence; Deep Learning; Vehicle detection; Vehicle tracking